HUKUM DAGANG DI INDONESIA (A REVIEW) - Rahayu, Siti; Roesli, Mohammad (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
The purpose of this research is to analyze and view the trade law in Indonesia. The technique of data collection in the form of document study, which is to research documents related to the problem that will be examined to obtain a theoretical basis and information in the form of formal provisions. Materials are analyzed using qualitative normative methods. The results showed that the trade law was the entire rule of law governing with the sanction of human deeds in their efforts to carry out the trade. The civil law relationship with the trading law can be seen from article 1 of the criminal CODE, which reads: "The provisions of the legal place shall also apply to the matters stipulated in the KUH of commerce, except where the KUH Dagang himself specifically arranged." In this connection is a valid Adagium "Lex specialist derogat Lex generalis" which is a particular law of defeating the common law. Since the Middle Ages of Europe (1000/1500) occurring in the country and cities of Europe and in those days in Italy and southern France have been born cities as trade centers (Genoa, Florence, Vennetia)